Examining the Influence of Online Social Networks and MOOCs on Collaborative Practices among TVET Teachers: The Mediating Role of Interpersonal Trust - Ameri, Mohammad Kazim; Mohammadi, Abeda (Integrated Journal for Research in Arts and Humanities, 2024)
This study examines the impact of online social networks (OSN) and Massive Open Online Courses (MOOCs) on collaborative practices among vocational training educators, focusing on the mediating role of interpersonal trust. Using a quantitative research design, Structural Equation Modeling (SEM) analyzed data from 343 Technical and Vocational Education and Training (TVET) teachers via a survey assessing MOOC usage, OSN, teacher collaboration, and interpersonal trust. Findings indicate a significant positive relationship between OSN and MOOCs, suggesting their potential to enhance collaborative learning environments. However, a negative direct effect of OSN on teacher collaboration reveals challenges that hinder effective engagement. Importantly, interpersonal trust is identified as a crucial mediator, highlighting the necessity of fostering trust among educators to improve collaboration and knowledge sharing. The research addresses a gap in understanding how MOOCs can enhance collaboration among TVET teachers and improve student outcomes, emphasizing the importance of integrating OSNs and MOOCs into vocational training frameworks while cultivating a culture of trust. Ultimately, the study suggests that leveraging OSNs and MOOCs, alongside interpersonal trust, can transform collaborative practices, benefiting both educators and students. Future research should explore the complexities of these relationships, especially barriers to collaboration and effective strategies for utilizing online networks in vocational training.